2006
DOI: 10.1016/j.clnu.2006.01.019
|View full text |Cite
|
Sign up to set email alerts
|

ESPEN Guidelines on Enteral Nutrition: Pancreas

Abstract: The two major forms of inflammatory pancreatic diseases, acute and chronic pancreatitis, require different approaches in nutritional management, which are presented in the present guideline. This clinical practice guideline gives evidence-based recommendations for the use of ONS and TF in these patients. It was developed by an interdisciplinary expert group in accordance with officially accepted standards and is based on all relevant publications since 1985. The guideline was discussed and accepted in a consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
170
0
23

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(194 citation statements)
references
References 63 publications
1
170
0
23
Order By: Relevance
“…A number of recommendations for the diagnosis and treatment of chronic pancreatitis have been published in different countries [1][2][3][4][5][6], but no systematic guidelines have been published up to now.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recommendations for the diagnosis and treatment of chronic pancreatitis have been published in different countries [1][2][3][4][5][6], but no systematic guidelines have been published up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to the old belief that pancreatic rest is important has significantly delayed the use of early enteral nutrition in severe pancreatitis. A large controlled study of patients with AP showed that enteral nutrition significantly reduced septic complications, but made no difference to the rate of multiple organ failure or death (Meier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, in several studies and guidelines, the superiority of EN/PN has been emphasized (McClave et al, 1997;Marik and Zaloga, 2004;Meier et al, 2006). PN is still a choice in patient who could not be fed orally or intolerant.…”
Section: Discussionmentioning
confidence: 99%
“…However, TPN is still a choice for the patients suffering from the mild AP with nausea and vomit (Meier et al, 2002(Meier et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%